Paris Africain - Winders, J. author. aut Link
XV, 231 p.
Keywords: The growth of African immigration to France at the end of the Twentieth Century wrought cultural change in this epicentre of the avant-garde in European art and music. James Winders presents the story of African immigrants to France as a unique chapter in the long history of the reception accorded expatriate artists in Paris.